Electro‐optic probe for real‐time assessments of RF electric field produced in an MRI scanner: Feasibility tests at 3 and 4.7 T. (12th November 2017) - Saniour, Isabelle; Gaborit, Gwenaël; Perrier, Anne‐Laure; Gillette, Laurane; Revillod, Guillaume; Sablong, Raphaël; Duvillaret, Lionel; Beuf, Olivier
Abstract : During magnetic resonance imaging (MRI) examinations, the average specific absorption rate (SAR) of the whole body is calculated as an index of global energy deposition in biological tissue without taking into account the presence of metallic implants or conductive materials. However, this global SAR calculation is not sufficient to ensure patient safety and a local SAR measurement should be carried out. Several measurement techniques have already been used to evaluate the local SAR, in particular electric field (E‐field) probes, but the accuracy of the measurements and the resolutions (spatial and temporal) depend strongly on the measurement method/probe. This work presents an MR‐compatible, subcentimeter probe based on an electro‐optic (EO) principle enabling a real‐time measurement of the local E‐field during MRI scans. The experiments using these probes were performed on two different MR systems (preclinical and clinical) having different static magnetic field strengths and with different volume coil geometries. The E‐field was measured with unloaded (in air) and loaded volume coils in order to assess the sensing characteristics of the optical probe. The results show an excellent linearity between the measured E‐field and the radiofrequency (RF) magnetic field in both experimental conditions. Moreover, the distribution of the E‐field throughout the volume coil was experimentally determined and was in good agreement with numerical simulations. Finally, we demonstrate through our measurements that the E‐field depends strongly on the dielectric properties of the medium. Abstract : The purpose of this study was to assess the performances of an optical‐based probe and its effectiveness in the detection of the electric field during magnetic resonance imaging (MRI) examinations. Using this subcentimeter probe, we were able to characterize radiofrequency (RF) coils by assessing the distribution of the electric field in the vicinity. We proved that this electro‐optic (EO) probe can be used at different B 0 strengths and coil geometries and in vitro with very low disturbance to the electromagnetic (EM) field.